2015
DOI: 10.4012/dmj.2014-255
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel fluorapatite-forming calcium phosphate cement with calcium silicate: <i>In vitro</i> and <i>in vivo</i> characteristics

Abstract: Aim of this study was to develop a novel fluorapatite-forming calcium phosphate cement (FA-CPC) with tricalcium silicate (TCS) for endodontic applications and to examine its in vitro and in vivo characteristics. The FA-CPC powder consisted of 62.8% CaHPO4, 30.8% CaCO3, and 6.4% NaF. One part of TCS was combined with 9 parts of FA-CPC powder (FA-CPC with TCS). A 1.5 M phosphate solution was used as cement liquid. Setting time (ST), diametral tensile strength (DTS), phase composition by X-ray diffraction (XRD), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The present results indicate that FA-forming CPC with TCS had excellent biocompatibility, similar to that of MTA. We recently reported that FA-forming CPC with TCS and MTA were highly biocompatible with rat subcutaneous connective tissue (14). The proliferation of ROS cells observed in the present study is consistent with our previous finding.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The present results indicate that FA-forming CPC with TCS had excellent biocompatibility, similar to that of MTA. We recently reported that FA-forming CPC with TCS and MTA were highly biocompatible with rat subcutaneous connective tissue (14). The proliferation of ROS cells observed in the present study is consistent with our previous finding.…”
Section: Discussionsupporting
confidence: 83%
“…The proliferation of ROS cells observed in the present study is consistent with our previous finding. In aqueous conditions, FA-forming CPC with TCS is almost entirely converted to FA within 24 h (14). FA typically has very high crystallinity, as compared with HA, and good biocompatibility with not only osteoblasts but also dental pulp cells, mesenchymal cells, and endothelial cells (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faster bone healing after periapical surgery for an apicoectomy is desired, as well as bone fusion in some instances. Calcium phosphate cements in combination with the other calcium cements may control resorption, 301,302 so that cervical resorption of teeth can be treated. Superabsorbent polymers [303][304][305] may be useful for creating bone tissue scaffolds using the calcium silicate cements.…”
Section: Future For Calcium Silicate and Calcium Aluminate Cementsmentioning
confidence: 99%